Complementary and alternative medicine use among patients with type 2 diabetes living in the United Arab Emirates - Radwan, Hadia (BMC Complement Med Ther, 2020)
BACKGROUND: The use of Complementary and Alternative Medicine (CAM) among Type 2 Diabetes Mellitus (T2DM) patients is increasing to manage the complexities of their condition, enhance their health, and ease complications. The burden of T2DM in the United Arab Emirates (UAE) coupled with the high prevalence of CAM use and its associated risks among patients with T2DM necessitated the investigation of the use of CAM by this patients’ population. The aim of this study is to examine the prevalence, types, and correlates of CAM use among T2DM patients in the UAE. METHODS: Patients with T2DM attending the outpatient clinics in the two governmental hospitals in Dubai and Sharjah, UAE were invited to participate in a cross-sectional survey. Face-to-face interviews were conducted with participants to complete a multi-component questionnaire. The questionnaire comprised of three main sections: demographic data, diabetes-related information, and CAM use details. Data analysis employed descriptive statistics, univariate and multivariate logistic regression to assess the prevalence and correlates of CAM use. RESULTS: Two hundred forty-four T2DM patients completed the questionnaire (response rate: 80%). A total of 39.3% of participants were CAM users since diagnosis. After adjustment; the logistic regression results showed that CAM use was significantly associated with age, sex, education, employment, and having health insurance. The most commonly used type of CAM by participants were folk foods and herbs followed by spiritual and natural healing and vitamins and minerals supplements. The majority of CAM users were referred or encouraged to use CAM by family (42.7%), friends (25%) or social media (17.7%). Only 13.5% of participants used CAM because it was suggested by health care practitioners. Only 1 in four of CAM users disclosed CAM use to their treating physician. CONCLUSION: CAM use among T2DM patients in the UAE is considerably high. Health policy and decision-makers are encouraged to dedicate particular attention to facilitating proper regulation and integration of CAM within conventional medicine to protect the health and wellbeing of patients. A concerted effort by medical schools and public health authorities should be committed to educating health care providers and patients on the safe and effective use of CAM therapies.